Recent advances of cyclin-dependent kinases as potential therapeutic targets in HR+/HER2− metastatic breast cancer: a focus on ribociclib - Edessa D (Dove Medical Press, 2017)
Dumessa Edessa,1 Mekonnen Sisay2 1Department of Pharmacy Practice, 2Department of Pharmacology and Toxicology, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Oromia, Ethiopia Abstract: In normal cell cycle progression, transition of G0/G1 phase to synthesis (S) phase for breast and other cells is regulated by association of cyclin D and cyclin-dependent kinases 4 and 6 (CDK4/6) that leads to phosphorylation of retinoblastoma (Rb) protein. Imbalance of this cyclin D-CDK4/6-inhibitors of CDK4/6-Rb phosphorylation pathway is associated with tumorigenesis of hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) breast cancers. Despite effective first-line endocrine therapy, HR+/HER2− metastatic breast cancers remain still incurable. Currently, advances in understanding of cell cycle checkpoints are evolving as promising strategy to target in treatment of various types of cancers including breast cancer. Therapies that target this cell cycle machinery in HR+/HER2− breast cancers are getting approval by the US Food and Drug administration (FDA) including ribociclib (LEE011). Ribociclib got the first FDA approval in March 13, 2017, as an initial therapy for HR+/HER2− advanced or metastatic breast cancer in combination with an aromatase inhibitor. This review, therefore, addresses the role of selective CDK4/6 inhibitors in advanced or metastatic breast cancer with a specific focus on ribociclib. Some findings of clinical trials involving ribociclib found pivotal benefits of ribociclib in HR+/HER2− metastatic breast cancer in terms of prolonging progression-free survival and objective response rates. Daily dosage range of the drug for such benefits is 50–900 mg with common daily doses of 400 or 600 mg and 600 mg in early and advanced breast cancer therapies, respectively. Along with its therapeutic benefits, however, more incident but manageable dose-limiting grade 3 or 4 toxicities, primarily hematologic adverse events, are common in patients treated with ribociclib. Generally, there are several active clinical trials undergoing to investigate the clinical efficacy and toxicity profile of the drug in various cancerous conditions other than breast cancer and will likely benefit patients with other cancer types. Keywords: cell cycle, cyclin-dependent kinase 4/6, HR+/HER2−, metastatic breast cancer, CDK4/6 inhibitors, ribociclib, LEE011